2021
DOI: 10.1111/mmi.14686
|View full text |Cite
|
Sign up to set email alerts
|

PaeA (YtfL) protects from cadaverine and putrescine stress in Salmonella Typhimurium and E. coli

Abstract: Salmonella and E. coli synthesize, import, and export cadaverine, putrescine, and spermidine to maintain physiological levels and provide pH homeostasis. Both low and high intracellular levels of polyamines confer pleiotropic phenotypes or lethality. Here, we demonstrate that the previously uncharacterized inner membrane protein PaeA (YtfL) is required for reducing cytoplasmic cadaverine and putrescine concentrations. We identified paeA as a gene involved in stationary phase survival when cells were initially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 75 publications
2
13
0
Order By: Relevance
“…In recent research, a previously uncharacterized membrane protein, PaeA (YtfL) of E. coli and Salmonella, was found to have a likely function in the efflux of the diamines putrescine and cadaverine. 417 Mutants of paeA were seen to accumulate higher concentrations of cadaverine and putrescine and are less tolerant to these diamines under defined environmental conditions. 417 Similar to proteins in the SMR and PACE families, PaeA is predicted to have four TM helices but it is significantly longer (∼450 amino acid residues) than proteins classified in either of these two families and contains defined extramembranous domains that are not seen in the SMR or PACE proteins.…”
Section: Polyamine Effluxmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent research, a previously uncharacterized membrane protein, PaeA (YtfL) of E. coli and Salmonella, was found to have a likely function in the efflux of the diamines putrescine and cadaverine. 417 Mutants of paeA were seen to accumulate higher concentrations of cadaverine and putrescine and are less tolerant to these diamines under defined environmental conditions. 417 Similar to proteins in the SMR and PACE families, PaeA is predicted to have four TM helices but it is significantly longer (∼450 amino acid residues) than proteins classified in either of these two families and contains defined extramembranous domains that are not seen in the SMR or PACE proteins.…”
Section: Polyamine Effluxmentioning
confidence: 99%
“…417 Mutants of paeA were seen to accumulate higher concentrations of cadaverine and putrescine and are less tolerant to these diamines under defined environmental conditions. 417 Similar to proteins in the SMR and PACE families, PaeA is predicted to have four TM helices but it is significantly longer (∼450 amino acid residues) than proteins classified in either of these two families and contains defined extramembranous domains that are not seen in the SMR or PACE proteins. Therefore, PaeA could represent a new class of polyamine export protein.…”
Section: Polyamine Effluxmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of pathogenicity factors identified ytfL , and relE transcripts within the majority of DFO samples. Iwadate et al reported that ytfL expression facilitates cell viability of E. coli and S. typhirium when exposed to polyamines such as putrescine and cadaverine, both of which are abundant within necrotic diabetes related foot ulcers (Iwadate et al, 2021 ). Previous studies have reported that relE overexpression results in reduced bacterial growth and increased persister cell formation in Xylella fastidiosa and E. coli (Tashiro et al, 2012 ; Burbank and Stenger, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms are known to trigger the expression of a specific battery of genes ( speF , cadA , cadB and paeA , etc. ), and specific polyamines synthesized are involved in, for example, the blockage of porins and a decrease in membrane permeability [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%